Pengaruh Disiplin Kerja dan Kerjasama terhadap Kinerja Pegawai pada Kantor Badan Pengelolaan Pajak dan Retribusi Daerah Propinsi Sumatera Utara UPT. Pematangsiantar - Mega Romauly Tampubolon; Calen Calen; Benjamin Albert Simamora; Juan A. Ongko (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
Competitive competition to achieve high performance does not only occur in private organizations, but also government. The formulation of the problem in this study is work discipline and cooperation on employee performance at the BPPRD Office of North Sumatra Province UPT Pematangsiantar. This research aims to determine work discipline and cooperation on employee performance at the BPPRD Office of North Sumatra Province UPT Pematangsiantar. The research design used by the author was field research, where the research was carried out at the BPPRD Office of North Sumatra Province UPT Pematangsiantar, the population was employees at the BPPRD Office of North Sumatra Province UPT Pematangsiantar. The sampling technique used saturated samples by using the entire population as the research sample, amounting to 43 employees. Data analysis techniques used multiple regression, hypothesis testing, coefficient of determination. The results showed that work discipline and cooperation have a positive effect on employee performance on the Employee Performance of BPPRD Office of North Sumatra Province UPT Pematangsiantar.